AKURASI HARGA POKOK PRODUKSI BERBASIS ACTIVITY-BASED COSTING SEBAGAI UPAYA EFISIENSI OPERASIONAL PADA UMKM TAPE BONDOWOSO - Nur Hamidah; Iis Riyana; Khofidatus Soliha; M. Sholehuddin; Enik Sulistyowati Enik (Universitas Nahdlatul Ulama Pasuruan, Indonesia, 2025)
This study aims to analyze the management of production costs in Bondowoso Tape MSMEs using the Activity-Based Costing (ABC) method as an effort to improve the accuracy of the calculation of Cost of Production (CoP), Cost of Goods Sold (CoGS), and Break-Even Point (BEP). The researcher collected data through interviews, observations, and documentation of financial statements which were then analyzed using a qualitative descriptive approach. The results show that the ABC method provides a more accurate cost allocation compared to the traditional method with details of the HPP of Mika Tape products of Rp. 5,147.39 per unit, while Small Tape is Rp. 3,601.93 per unit. BEP was achieved for Mika Tape at 19,821 units and for Small Tape at 3,944 units, while the profit and loss report indicated a net profit of Rp. 34,960,318.38 for Mika Tape and Rp. 70,672,831.34 for Small Tape, so it can be concluded that the research using the ABC method is able improve cost efficiency and provide a basis for strategic decision-making for Tape Bondowoso MSMEs.. Keywords: Activity-Based Costing, Cost Of Production, Break-Even Point, MSMEs.